2014
DOI: 10.1098/rsif.2014.0638
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic adaptability of cancer cells strongly affects anti-migratory drug efficacy

Abstract: Cancer metastasis involves the dissemination of cancer cells from the primary tumour site and is responsible for the majority of solid tumour-related mortality. Screening of anti-metastasis drugs often includes functional assays that examine cancer cell invasion inside a three-dimensional hydrogel that mimics the extracellular matrix (ECM). Here, we built a mechanically tuneable collagen hydrogel model to recapitulate cancer spreading into heterogeneous tumour stroma and monitored the three-dimensional invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 56 publications
0
29
0
Order By: Relevance
“…We anticipate that the presence of directional chemotactic stimuli or biochemical gradients will increase the persistence, potentially in collagen concentration-dependent manner. Furthermore, we also observed that the mean speed of cell migration did not significantly change with collagen concentration (Figure 4D), likely because of the interplay between matrix stiffness (which increases with collagen concentration) and pore size (which decreases with collagen concentration) 10 , as well as the spatiotemporal variation of migration characteristics within the cell population 7 . The mean speed varied between 31 µm/hr and 37.5 µm/hr, with a minimum individual cell speed of 7 µm/hr and a maximum individual cell speed of 114 µm/hr.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…We anticipate that the presence of directional chemotactic stimuli or biochemical gradients will increase the persistence, potentially in collagen concentration-dependent manner. Furthermore, we also observed that the mean speed of cell migration did not significantly change with collagen concentration (Figure 4D), likely because of the interplay between matrix stiffness (which increases with collagen concentration) and pore size (which decreases with collagen concentration) 10 , as well as the spatiotemporal variation of migration characteristics within the cell population 7 . The mean speed varied between 31 µm/hr and 37.5 µm/hr, with a minimum individual cell speed of 7 µm/hr and a maximum individual cell speed of 114 µm/hr.…”
mentioning
confidence: 67%
“…It is now possible to obtain spatially-resolved viscoelastic measurements of the local matrices surrounding the cells using microrheological approaches 19 . Furthermore, our recent study 10 reveals that the efficacy of various anti-migratory drugs (administered on the 7 th day of the experiment) can be strongly affected by the architecture and stiffness of the matrix (i.e., outer gel). In the future, we plan to use these experimental frameworks to further understand how such effects can arise from the basic molecular mechanisms of cell migration (e.g., cytoskeletal contractility 20 , extracellular matrix reorganization 21 , and pericellular proteolysis 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations